2019
DOI: 10.3390/ma12071041
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Porosity on the Mechanical Behavior during Uniaxial Compressive Testing on Voronoi-Based Open-Cell Aluminium Foam

Abstract: We have studied an application of the Voronoi tessellation method in the modeling of open-cell aluminium foam under uniaxial compressive loading. The Voronoi code was merged with computer-aided design (CAD) for converting the polyhedral model into an irregular open-cell cellular structure to create porous samples for compression testing simulations. Numerical simulations of the uniaxial compression uniformly over the upper surface of the sample in the z-axis direction at a constant 20 N load was realised. Samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Similarly, von Mises stress was used in the evaluation of porous materials in many studies in the literature. 41,5359 Moreover, the von Mises stresses on the implanted hip stem are an important indication in assessing the transfer of load from the hip implant stem to the femoral bone. 38 However, it may be misleading to use only the maximum von Mises values when evaluating this load transfer phenomenon, especially in hip implant stem having lattice designs.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, von Mises stress was used in the evaluation of porous materials in many studies in the literature. 41,5359 Moreover, the von Mises stresses on the implanted hip stem are an important indication in assessing the transfer of load from the hip implant stem to the femoral bone. 38 However, it may be misleading to use only the maximum von Mises values when evaluating this load transfer phenomenon, especially in hip implant stem having lattice designs.…”
Section: Resultsmentioning
confidence: 99%
“…In their study, the critical load of the Voronoi designed porous structures was increased by nearly 300%, which showed the ability for internal load-bearing implant structure. For another model built with algorithm, the results also showed that the manufactured model exhibited a high load to weight ratio, which is a crucial parameter for the scaffold (shown in Figure 2D) (Sharma et al, 2019). Voronoi designed scaffold with gradient porosity (60% to 95%) also showed excellent mechanical properties.…”
Section: Based On Voronoimentioning
confidence: 86%
“…As the porosity increases, the contact surface area decreases which causes sudden increase in stresses as a result of reduced foam strength. 48 Highest tensile strength was observed for wax powder foaming agent whose value equal to 6.16 MPa at a deformation rate of 4.4, followed by magnesium hydroxide of 5.32 MPa at a deformation rate of 4, and TiH 2 equal to 4.3 MPa and deformation of 3.5, respectively (refer Figure 7 and Table 2). Reduced strengths observed with magnesium hydroxide and titanium hydride are attributed to higher porosity in foam samples.…”
Section: Tensile Strength Behavior On Aluminum Metal Foam With Differ...mentioning
confidence: 94%